Phenotypic mismatch between suspects and fillers but not phenotypic bias increases eyewitness identifications of Black suspects - Jones, Jennifer M.; Katzman, Jacqueline; Kovera, Margaret Bull (Frontiers in Psychology, 2024)
In many contexts, people exhibit a phenotypic bias, more closely associating the construct of criminality with Black people who exhibit a more African facial phenotype than with Black people who express a more European phenotype. The current study tested whether this phenotypic bias extended to eyewitness identification tasks, with eyewitnesses more likely to identify Black suspects with an African rather than a more European phenotype. We also tested whether lineup composition (suspect's phenotype matched vs. mismatched the phenotype of the other people appearing in the array) and the presentation method (simultaneous vs. sequential) moderated the expression of phenotypic bias. We predicted that that when lineups were presented simultaneously, there would be a significant two-way interaction of phenotypic bias and lineup composition, with a larger simple main effect of phenotypic bias when lineups were suspect-biased (i.e., the fillers were a phenotypic mismatch to the suspect) than when all lineup members shared the same phenotype. We expected that this interaction would be significantly smaller or non-significant for sequential lineups. Participants watched a mock crime video with culprits that varied in their expression of a more African phenotype before attempting identifications from photo arrays that varied in culprit-presence, suspect phenotype, phenotypic match of suspect and fillers, and presentation method. Participants did not identify Black suspects with Afrocentric features more often than Black suspects with Eurocentric features. However, witnesses made more identifications of suspects when the fillers did not match the suspect's phenotype compared to when all lineup members possessed similar phenotypic features. In sum, phenotypic bias did not influence our participant-witnesses' identification decisions, nor interact with lineup composition and lineup presentation type to affect identifications of suspects, suggesting that phenotypic bias may be less influential in match-to-memory tasks than other types of legal decision making (e.g., determining guilt, sentencing). However, the suggestiveness created by failing to match fillers' phenotypes to the suspect's phenotype can be avoided with proper attention to fair lineup construction.